“We Need a Bit of Trumpism”: Anger and Resentment in Austerity Italy - Antonio Maria Pusceddu (Antropologia)
In this article, I look at anger and resentment as intertwined feelings underlying popular reactions to the perception of state failure in tackling social disparities. I adopt a perspective that articulates the anthropological study of the state with the Gramscian theorization of the integral state. I examine how anger and resentment shape the everyday perceptions of politics in the urban periphery of Brindisi. I organize my analysis around the examination of a corruption scandal that led to the arrest of the mayor, which I deploy as the prism to explore popular relatedness to the state, highlighting the “disconnection of feeling” between the political elite and popular classes. I argue that by framing the resentful feelings of the latter through the idea of disconnection, we can advance a useful description of people’s relatedness to the state in the current historical conjuncture.